Shelf and open-ocean calcareous phytoplankton assemblages across the Paleocene-Eocene Thermal Maximum: Implications for global productivity gradients - Gibbs, SJ; Bralower, TJ; Bown, PR; Zachos, JC; Bybell, LM (GEOLOGICAL SOC AMERICA, INC, 2006)
Abrupt global warming and profound perturbation of the carbon cycle during the Paleocene-Eocene Thermal Maximum (PETM, ca. 55 Ma) have been linked to a massive release of carbon into the ocean-atmosphere system. Increased phytoplankton productivity has been invoked to cause subsequent CO2 drawdown, cooling, and environmental recovery. However, interpretations of geochemical and biotic data differ on when and where this increased productivity occurred. Here we present high-resolution nannofossil assemblage data from a shelf section (the U.S. Geological Survey [USGS] drill hole at Wilson Lake, New Jersey) and an open-ocean location (Ocean Drilling Program [ODP] Site 1209, paleoequatorial Pacific). These data combined with published biotic records indicate a transient steepening of shelf-offshelf trophic gradients across the PETM onset and peak, with a decrease in open-ocean productivity coeval with increased nutrient availability in shelf areas. Productivity levels recovered in the open ocean during the later stages of the event, which, coupled with intensified continental weathering rates, may have played an important role in carbon sequestration and CO2 drawdown.